MBO 在中国上市公司应有的探索 = Applying the management buyouts China listed company - 沈荣 Sheng, Rong (2008)
Discussion regarding the necessity of management buyouts as the basis of corporate-governance theory, the legal risks of such management buyouts and how to avoid them.